Improving Distance Learners’ Writing Skills Through Comic Strip Creation: A Project-Based Learning - Lailatul Abidah; Mifta Libby Askangela; Declarieta Berlianty; Ria Arista Asih (Universitas Pahlawan Tuanku Tambusai, 2022)
Students’ difficulties in mastering writing skills are exacerbated by teachers’ limited instruction in writing classes due to the COVID-19 pandemic. The present study aims to find out whether Project-Based Learning (PjBL) is effective in increasing distance learners’ writing skills and motivation to learn. This study employed the Classroom Action Research (CAR) method involving 13 students of twelfth-grade SMKN 1 Bungaraya, chosen through one-stage cluster sampling. This research was conducted online, synchronously, and asynchronously. The questionnaire, observation, and test results show that the PjBL approach allows students to be more engaged and creative in distance learning. The implementation of PjBL through comic strip creation has also driven students to increase their writing skills. It was evidenced by the increase in the student’s scores. The pretest score was 60.53, which increased after post-test I to 70.77, and continued to increase to 80 at the end of Cycle II.